High-parameter immune profiling and subjective health assessment of the immunomodulatory effects of paramylon-rich Euglena gracilis EOD-1: A randomized, double-blind, placebo-controlled, parallel-group study - Takanori Kawano; Atsushi Miura; Junko Naito; Norihisa Nishida; Ken-ichi Ishibashi; Yoshiyuki Adachi; Naohito Ohno; Yuji Naito (Journal of Functional Foods, 2023)
Paramylon, a characteristic β-glucan of microalgae Euglena gracilis, modulates immune function. However, data on its mechanism of action and use in humans are limited. We conducted a 12-week randomized controlled trial to determine the effects of paramylon-rich E. gracilis EOD-1 (PM EOD-1) ingestion on immune function and physical condition by randomly assigning 24 healthy men and women (50–65 years old) to PM EOD-1 (PM 350 mg) or placebo groups. We evaluated physical condition, cytokine proteomics, and high-parameter immune profiling. The PM EOD-1 group exhibited a higher number of cumulative good health days, increased or sustained high IL17A, IL27, CSF2, FLT3LG, and IL17C levels, increased CD28 expression in CD4+/CD8+ naïve T cells, and maintained CD80 expression in monocytes than the placebo group. PM EOD-1 promotes immune cell response potential by enhancing monocyte activation and co-stimulatory molecule interactions between T and antigen-presenting cells, thereby promoting immune defense and good health.